Pengaruh Penggunaan Chat-GPT (Generative Pre-Trained Transformer) Sebagai Sumber Belajar Terhadap Pengetahuan Kewarganegaraan Peserta Didik pada Mata Pelajaran PPKn - Maulana, Muhammad Sunan; Nida, Qotrun; Fitrayadi, Dinar Sugiana (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the effect of using Chat-GPT (Generative Pre-Trained Transformer) as a learning resource on students' civic knowledge in Civics subjects at SMAN 1 Cilegon, school year 2024/2025. Using quantitative methods with correlational statistical techniques, the research population was class XI students and the sample was taken by cluster random sampling. The results showed that there was a significant influence and correlation between the use of Chat-GPT as a learning resource on civic knowledge with a significance value of 0.001 0.05, meaning that there was a correlation between the two variables and r count 0.600 r table 0.214 indicating that there was a positive influence. For the coefficient of determination (R Square), the result of 0.360 shows that the effect of using Chat-GPT as a learning resource on students' civic knowledge is 36% So it can be concluded that there is a positive influence on the use of Chat-GPT (Generative Pre-Trained Transformer) as a learning resource (X) on students' civic knowledge (Y) in Civics subjects at SMAN 1 Cilegon.